Pengaruh Dukungan Orang Tua dan Fasilitas Belajar Terhadap Hasil Siswa Kelas X SMAN 9 Kota Jambi - Sembiring, Benar; Azwari, Putri Anadia (SJEE (Scientific Journals of Economic Education), 2025)
This research aims to find out influence of parental support and learning facilities on the learning outcomes of class X students at SMAN 9 Jambi City. The research method used in this research is a quantitative method using multiple linear regression analysis techniques. The research results show that there is an influence between parental support and learning facilities on the learning outcomes of class X students at SMAN 9 Jambi City. So, students with support from their parents in providing encouragement tend to be in the form of motivation, meeting the learning needs and completeness of students in their learning process, but due to the lack of provision of adequate learning media to support the learning process. Therefore, it is important to pay attention to and improve learning facilities to support student success in achieving good learning outcomes.